Война и мир - Толстой Лев Николаевич (100 главных книг, 2015)
Экземпляры: 25 (20150923) / Инвентарный номер: 59985 / Цена: 238.00 / Сис.шифр: Р1 / Авт.знак: Т-53 / ГРНТИ: 17.82.31 / ББК: 84 (2Рос=Рус)